The Akkadian and Sumerian texts from Ortaköy-Šapinuwa - Schwemer, Daniel, 1970- (Wiesbaden)
xii, 93 sayfa, xxxviii sayfa resim
Keywords: “The Hittite site near the town Ortaköy (Çorum Province, Turkey) has been the subject of archaeological investigations since 1990 and has produced a large number of cuneiform text finds from the Early Empire period of the Hittite kingdom (14th cent. BCE). The texts show that the site is to be identified with the Hittite city of Šapinuwa, which served as royal residence and capital of the Hittite kingdom during the reign of Tutḫaliya II. In the present volume Aygül Süel, the director of the excavations, and Daniel Schwemer publish the Akkadian and Sumerian tablets and fragments from Ortaköy-Šapinuwa, which were mainly found in the palace archives of Šapinuwa. The texts display the full range of motivations and contexts of writing Akkadian and Sumerian in Hittite Anatolia, including Sumerian lexical texts and Akkadian literary fragments of primarily scholastic interest, Akkadian devotional texts that were adapted for the religious practice of the Hittite royal family, as well as fragments of the Akkadian diplomatic correspondence of the Hittite king. The volume is bilingual and offers all texts in English and in Turkish“ --